Prognostic Value of Long Noncoding RNA SNHG11 in Patients with Prostate Cancer - Li, Ying; Pan, Bin; Guo, Xiuqin; Meng, Xiaomin; Tian, Xiaojing (Hormone and Metabolic Research, 2022)
The present study was aimed to explore the prognostic value of long noncoding RNA SNHG11 in prostate cancer, study its expression, and assess its effect on tumor progression. One hundred and twenty prostate cancer patients and 45 cases of benign prostate hyperplasia (BPH) patients were collected. RT-qPCR was used to test the expression of SNHG11 in prostate cancer and BPH tissues, as well as in cell lines. Kaplan-Meier survival analysis and Cox regression assays were introduced to evaluate the prognostic meaning of SNHG11 in prostate cancer. The CCK-8 assays were performed to explore the effect of SNHG11 on prostate cancer cell proliferation, and a Transwell assay was conducted to access the influence of SNHG11 on prostate cancer cell migration and invasion. SNHG11 expression level was upregulated both in prostate cancer tissues and cell lines. Overexpression of SNHG11 was significantly associated with Gleason score, clinical T stage, surgical margin status, and lymph node metastasis. Patients with high SNHG11 expression levels led to a shorter overall survival time and biochemical recurrence-free survival when compared with those of low expression levels. Multivariate Cox regression results suggested that SNHG11 has the potential to act as a prognostic marker for prostate cancer patients. Knockdown of SNHG11 suppressed 22RV1 cell proliferation, migration, and invasion. In conclusion, SNHG11 is upregulated in prostate cancer patients and predicts an unfavorable prognosis for prostate cancer patients. Its knockdown can weaken prostate cancer cell metastasis and growth in vitro.
Keywords: prognosis; SNHG11; prostate cancer; proliferation; invasion